Climatic drivers for multidecadal shifts in solute transport and methane production zones within a large peat basin. Issue 11 (3rd November 2016) - Glaser, Paul H.; Siegel, Donald I.; Chanton, Jeffrey P.; Reeve, Andrew S.; Rosenberry, Donald O.; Corbett, J. Elizabeth; Dasgupta, Soumitri; Levy, Zeno
Abstract: Northern peatlands are an important source for greenhouse gases, but their capacity to produce methane remains uncertain under changing climatic conditions. We therefore analyzed a 43 year time series of the pore‐water chemistry to determine if long‐term shifts in precipitation altered the vertical transport of solutes within a large peat basin in northern Minnesota. These data suggest that rates of methane production can be finely tuned to multidecadal shifts in precipitation that drive the vertical penetration of labile carbon substrates within the Glacial Lake Agassiz Peatlands. Tritium and cation profiles demonstrate that only the upper meter of these peat deposits was flushed by downwardly moving recharge from 1965 to 1983 during a Transitional Dry‐to‐Moist Period. However, a shift to a moister climate after 1984 drove surface waters much deeper, largely flushing the pore waters of all bogs and fens to depths of 2 m. Labile carbon compounds were transported downward from the rhizosphere to the basal peat at this time producing a substantial enrichment of methane in Δ 14 C with respect to the solid‐phase peat from 1991 to 2008. These data indicate that labile carbon substrates can fuel deep production zones of methanogenesis that more than doubled in thickness across this large peat basin after 1984. Moreover, the entire peat profile apparently has the capacity to produce methane from labile carbon substrates depending on climate‐driven modes of solute transport. Future changes in precipitation may therefore play a central role in determining the source strength of peatlands in the global methane cycle. Key Points: Methane production zones are finely tuned to climate‐driven transport systems in a 7600 km 2 peat basin During dry decades, a weak recharge regime restricts CH4 production to shallow peat depths During wetter decades, deeper recharge extends CH4 production to the entire peat profile